Exploring Nuances of EFL Student Engagement in Game-Based English Learning: A Qualitative Case Study - Israfil, Muhammad; Roslaini (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
English language learning plays an important role in developing EFL students' competencies in the era of globalization, yet low student engagement remains a major challenge due to monotonous learning methods. This study aims to investigate how Game-Based Learning (GBL) enhances students' engagement as well as explore their experiences during the learning process. Using thematic analysis, the findings show that GBL encourages behavioural engagement through active participation, collaboration, and adherence to game rules; emotional engagement through fun, enthusiasm in group learning, and excitement during competition; and cognitive engagement through increased curiosity, use of strategies, and reflection on self-development. The implications of this study suggest that teachers need to integrate game elements that support peer teaching, emotional safety and strategic thinking - such as time-based group games or language puzzles - tailored to students' ability levels to create more inclusive, fun and meaningful learning.